Analysis of Deol Chagi Kick Accuracy in Athletes from Tamarunang Taekwondo Club Yon Armed 6/3 Kostrad Makassar - Andi Nur Aisyah; Hikmad Hakim (Indonesian Journal Of Physical Activity and Sport Development (IJPASD), 2024)
Taekwondo is a Korean martial art that uses bare feet and hands to destroy targets, which is increasingly popular in Indonesia. Technological developments have simplified the kyorugi match system in taekwondo martial arts through the Protector Scoring System (PSS), which gives points based on the accuracy of the kick with impact on the target or sensor. The deol chagi kick is a straight forward kick that is done by lifting the leg linearly which is jerked straight down like an axe movement targeting the head. This study aims to analyze the accuracy of the Deol chagi kick of Tamarunang Taekwondo Club Yon Armed 6/3 Kostrad Makassar athletes. The research method is a quantitative approach with a survey assessment type. The sample used was 20 female athletes selected using the purposive sampling technique. Data collection was carried out through tests and measurements of kick accuracy. The results of the data analysis showed that the average value of the level of accuracy of the Deol chagi kick of Tamarunang Taekwondo Club athletes with the highest frequency was in the moderate category.